Multiple Sclerosis Patient Management During the COVID-19 Pandemic: Practical Recommendations From the Portuguese Multiple Sclerosis Study Group (GEEM) - Cerqueira, João J.; Ladeira, Ana F.; Silva, Ana M.; Timóteo, Ângela; Vale, José; Sousa, Lívia; Arenga, Marta; Abreu, Pedro; Guerreiro, Rui; de Sá, João (Frontiers in Neurology, 2021)
The spread of the COVID-19 pandemic has imposed significant challenges on healthcare provision, requiring changes in the conventional patient management, particularly in chronic diseases like multiple sclerosis (MS). To increase patient safety and reduce the risk of infection, while ensuring an appropriate and regular follow-up, tele-medicine gained prominence as a valid alternative to face-to-face appointments. However, the urgency of the implementation and the lack of experience in most MS centers led to “ad hoc” and extremely diverse approaches, which now merit to be standardized and refined. Indeed, while tele-consultation cannot fully replace face-to-face visits, it certainly can, and will, be incorporated as part of the routine care of MS patients in the near future. Bearing this in mind, the Portuguese Multiple Sclerosis Study Group (GEEM) has developed a set of recommendations for the usage of tele-medicine in the management of MS patients, both during the pandemic and in the future. The consensus was obtained through a two-step modified Delphi methodology, resulting in 15 recommendations, which are detailed in the manuscript.